Assessment of Compliance in Hypertensive and Diabetic Patients at Primary Health Care: A Prospective Study - Nagavi, Jinesh Bahubali; Kumar, Sahana Krishna; Shivamallaiah, Lakshmi; Meenakshi, Chandra Sekar (Indian Journal of Pharmacy Practice)
Background: Recent data in India have identified 77 million people as having diabetes (8.9% prevalence in 20-79 years), and these numbers are expected to increase to 100 million by 2030. Nearly 30% of Indians have hypertension, and only one-tenth of the rural and one-fifth of the urban Indian hypertensive population have their Blood Pressure [BP] under control. Therefore, medication adherence, knowledge and attitude towards disease and patient counselling play a crucial role in the maintenance of the disease condition. Aims: To study the effect of clinical pharmacist inclusion for betterment of patient adherence to medication. Materials and Methods: A cross-sectional community-based survey was carried out on 100 participants with diabetes and hypertension at primary health centres to assess treatment compliance. A peer reviewed questionnaire was used to collect the details by community pharmacists which included particulars on health records, medications and factors assessing the acquiescence, understanding and perspective towards the disease. Relevant data was transferred into an Excel sheet and results were assessed using SPSS statistical tool. Results: Among the 100 patients considered for the study, 43% were diabetic, 37% were only hypertensive and the remaining 20% were both diabetic and hypertensive. Among the study population of diabetic patients, only 43.05% of patients had their blood glucose level under control and only 5% of the hypertensive population had their blood pressure under control. 66% of the selected patients were compliant and the other 34% self-reported partial compliance. Conclusion: The most prevalent factors for non-compliance was indolence and most mentioned forgetting to take the medication due to negligence or pre-occupation. Lifestyle modifications performed by over 80% of study patients included-fast walk, yoga and meditation. Around 92% of study population reportedly kept track of their conditions on a regular basis. This study demonstrates the need for clinical pharmacists to be included as an essential member of the healthcare team to improve patient outcomes in India.
Keywords: Anti-diabetic; Anti-hypertensive; Compliance; Hypertension; Diabetes